2013
DOI: 10.5861/ijrset.2013.363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of advanced organizers on attainment and retention of students’ concept of gravity in Nigeria

Abstract: This study on the effects of advanced organizers on attainment and retention of students' concept of gravity in Nigeria was carried out to find out the efficacy of using advanced organizers to teach students the concepts of gravitation, weightlessness and space travels which are topics the students of junior secondary one have not been previously taught. 80 junior secondary one students from two secondary schools in Delta state Nigeria were used for the study. The students were grouped into two; the advanced-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Maryam, Moenikia and Zahed-Babelan (2010) argue that advance organizers are effective ways to facilitate the task because they can provide an overview of a new topic and visually represent links between the concepts to be learned. A study by Atomatofa (2013) revealed that Advance lead to improved students' achievement and retention than those taught using conventional teaching methods. Advance organizers are cognitive bridges, which teachers use to help learners make a link between what they know and what is to be learnt (Novak, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Maryam, Moenikia and Zahed-Babelan (2010) argue that advance organizers are effective ways to facilitate the task because they can provide an overview of a new topic and visually represent links between the concepts to be learned. A study by Atomatofa (2013) revealed that Advance lead to improved students' achievement and retention than those taught using conventional teaching methods. Advance organizers are cognitive bridges, which teachers use to help learners make a link between what they know and what is to be learnt (Novak, 1980).…”
Section: Introductionmentioning
confidence: 99%